On the taxonomy of the subgenus Gigantovulpecula Karisch, 2013 of the genus Cyana Walker, 1854, with description of a new species (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V. (Zootaxa, 2020)
The subgenus Gigantovulpecula Karisch, 2013 of the genus Cyana Walker, 1854 endemic for Madagascar is overviewed. Cyana saalmuelleri pauliani (de Toulgoët, 1954) is upgraded to the species level: C. pauliani (de Toulgoët, 1954), stat. nov. A new species is described from Central Madagascar: C. detoulgoeti Volynkin, sp. n. The second species associated with Gigantovulpecula, C. grandis Mabille, 1879 is synonymized with Cyana arama (Moore, 1859) known from India, Nepal and W China, and it is stated that its type locality, Madagascar is wrong and probably based on the mislabeled type specimen.